(untitled) (Journal of Health Sciences, 2013)
Introduction: A person’s response and functioning under condition of stress and confl ict is fundamentally different from its usual behavior. Aim: To point out what type of attitude toward the management of healthcare institutions is worth developing as well as to determine which psychological dimensions of employed the best refl ect the efficacy of the management.Methods: The study included a sample of 52 subjects employed at the Clinical center at University of Sarajevo and 64 subjects employed in Healthcare clinic in Sarajevo Canton. Survey method and a method of a theoretical analysis were used in the data collection and processing.Results: The study concluded that there is no statistically significant gender difference in attitude about the value of talent development at managerial level as a factor in development of attitude toward communicationin healthcare. We find t-value of 2,213 for the Clinical center at University of Sarajevo and 2,210 for Healthcare clinic in Sarajevo Canton.Conclusion: No statistically significant results have been found for any of the factors considered in the study with respect to the gender differences.